Limited impacts of the fungus Syncephalastrum on nests of leaf-cutting ants - Bautz, Keminy R.; Caixeta, Marcela C.S.; Del Puppo, Nathalia P.; Rodrigues, André [UNESP]; Kloss, Thiago G.; Elliot, Simon L. (Elsevier, 2023)
Leaf-cutting ants interact naturally with a range of antagonistic microorganisms, among them the soil-borne fungus Syncephalastrum. The antagonism of this fungus to the leaf-cutting ants’ fungal cultivar has been shown in studies without the ant queens. So far, the impacts of this fungus on whole colonies (queenright) of leaf-cutting ants are unknown. We assessed the impacts of Syncephalastrum on queenless and queenright colonies of Acromyrmex subterraneus subterraneus. In general, Syncephalastrum negatively impacted leaf cutting but not midden production or colony weight. This impact was greater in queenless colonies. Nevertheless, it did not compromise the survival of any colony. This indicates that the virulence of this fungus to leaf-cutting ant colonies may be limited in a more realistic set-up than previously reported. We propose that future laboratory studies also use queenright colonies where possible, and that the diverse species of leaf-cutting ants also be considered.
Keywords: Acromyrmex; Fungus garden; Host-parasite interactions; Leaf-cutting ants; Queen; Virulence